(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Decrease quantity of sections of the casing saves time and money in the process of fastening of the well. The need to use the sectional descent columns caused by a not sufficient capacity drilling rigs, mainly. In addition, casings domestic and imported can not withstand the loads created by the weight of its own huge casing. In general, to address the issue of development reduce the quantity of sections descent columns are developing in two directions: increasing the carrying capacity of drilling rigs, the creation of special jacks for running casing; increasing buoyancy force acting on the column in the wash liquid. The first way allows for the descent into the well casing heavy and has only one limitation on unscrews loads in threaded connections. In applying of welded columns is limiting the tensile stresses along the pipe. The second way is more technically difficult and needs of additional equipment casing and introduces additional limitations. The first method shutter casing at one time is limited and the real unscrew load. In the second method sectional casing shutter is reduced by 30 – 60%. Keywords: drilling column, borehole, drilling fluid, centralizer.